Stocks hedge against inflation in the long run: evidence from a cointegration analysis for Denmark - Jan Overgaard Olesen (Copenhagen Business School (CBS), Department of Economics, 2000)
We suggest an alternative approach to testing whether stocks provide a hedge against inflation in the long run. Based on a simple structural model, we test the hedge hypothesis in terms of the long-run linkage between stock prices and the general price level, as estimated by cointegration analysis. Using data for the Danish stock market over the post-World War II-period, results give strong support for the hedge property, defined in the narrow sense of a perfect hedge. This contrasts with the weak support found in the literature and also represents stronger support than produced by standard methods. We argue that our approach has the advantage of allowing for a clear distinction between short- and long-run dynamics of stock prices which adjust slowly to long-run equilibrium.
hdl:10398/7557
Keywords: G11; 330; Stocks; Hedge; Inflation; Denmark; Stock prices